Perkembangan Sensitizer pada Terapi Fotodinamika Tumor dan Kanker Hingga Penuntunan Nanopartikel (Nanoparticulate Targeting) Dengan Antibodi Monoklonal - INDRAWATI, RENNY; KARWUR, FERRY F; LIMANTARA, LEENAWATY (Indonesian Journal of Cancer, 2010)
World Health Organization (WHO) estimates both the number of patients and mortality rates due to cancer will continue to rise. Various researches were conducted in order to prevent and handle the cases of tumors and cancers, including the application of photosynthetic pigment molecules known as photodynamic therapy (PDT). Chlorophylls, the main pigment in photosynthesis, have an ability to capture light energy and control series of photobiology and photochemical processes1. In PDT, chlorophyll or its derivatives compounds act as the sensitizer which have energy excitation by light radiation (visible or near infra red), and generate some reactive oxygen species which triggers the death of cancer cells selectively (through apoptosis and / or necrosis pathway)2. Sensitizer compounds have been progressing from the first to third generation. The development of the third generation sensitizer was influenced by the advances of nanotechnology which lead to the improvement of PDT efficacy. The structure and size of nanoparticles can increase light absorption, and make the sensitizer accumulate in cancer tissues more specifically 3-4. Furthermore, nanoparticulatte targeting also interested to be studied because by conjugate functional groups, i.e. monoclonal antibody, on the sensitizer, it can improve the selectivity of therapy in targeting tumor and cancer tissues.